Intervensi Psikologi Positif Meningkatkan Psychological Well-Being pada Dewasa Awal yang Mengalami Quarter Life Crisis - Halif Alifatawloh; Nafisa Azahra; Novita Tri Handayani; Saskia Marisa; Zahra Rafifah (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Quarter life crisis is a developmental crisis commonly experienced by individuals in early adulthood, characterized by feelings of anxiety, confusion, self-doubt, and uncertainty about future life directions. This condition may reduce psychological well-being, making appropriate interventions necessary to improve individuals' well-being. This study aimed to examine the effectiveness of a positive psychology intervention in improving the psychological well-being of early adults experiencing quarter life crisis. The study employed a quantitative approach using a One Group Pretest–Posttest Design. The participants consisted of seven early adults aged 20–30 years who were selected through purposive sampling. The research instrument was the Psychological Well-Being Scale based on Carol D. Ryff's theory, which measures six dimensions: self-acceptance, positive relations with others, autonomy, environmental mastery, purpose in life, and personal growth. The positive psychology intervention was conducted over four sessions, including psychoeducation, self-reflection, strength identification, group discussions, and goal-setting activities. The results showed an increase in the average psychological well-being score from 65.83 in the pretest to 70.33 in the posttest, with an average improvement of 4.50 points. All participants who completed the posttest demonstrated increased scores. Observational findings also indicated greater openness, active participation, improved self-reflection, and clearer life goals among participants. These findings suggest that positive psychology interventions have the potential to enhance the psychological well-being of early adults experiencing quarter life crisis.